2016
DOI: 10.12659/msm.898908
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of miR-26a and Pleomorphic Adenoma Gene 1 (PLAG1) in Invasive Pituitary Adenoma

Abstract: BackgroundAlthough pituitary adenoma is a malignant tumor, it can present as invasive growth in some cases. MicroRNA (miR)-26a has been found to be abnormally highly expressed in pituitary adenoma, indicating possible involvement in pathogenesis. As a known target gene of miR-26a, PLAG1 has abnormally low expression in pituitary adenoma. The correlation between miR-26a or PLAG1 expressional abnormality and occurrence of pituitary adenoma is still unknown, as is its association with invasiveness of pituitary ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
(2 reference statements)
0
15
0
3
Order By: Relevance
“…miRNAs function as key regulators of gene expression via binding to the 3'-untranslated region (UTR) of the target mRNAs, and consequently inducing the degradation or translation inhibition of the mRNAs (5,7,8). Notably, emerging evidence has illustrated the critical roles of miRNAs in the pathogenesis of different cancer types (9)(10)(11)(12)(13)(14)(15)(16). For example, miR-106b targeted the tumor suppressor phosphatase and tensin homolog and promoted the growth of pituitary cancer cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs function as key regulators of gene expression via binding to the 3'-untranslated region (UTR) of the target mRNAs, and consequently inducing the degradation or translation inhibition of the mRNAs (5,7,8). Notably, emerging evidence has illustrated the critical roles of miRNAs in the pathogenesis of different cancer types (9)(10)(11)(12)(13)(14)(15)(16). For example, miR-106b targeted the tumor suppressor phosphatase and tensin homolog and promoted the growth of pituitary cancer cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more evidences have shown that miRNA plays a key regulatory role in tumorigenesis and development. 5,7 For instance, miRNAs are found to affect cell differentiation, proliferation, and apoptosis by reducing the stability of target genes or inhibiting their translation. 27,28 Exploring the relationship between miRNAs and BC formation provides a new way to define the pathogenic factors of BC.…”
Section: Discussionmentioning
confidence: 99%
“…It is a family of noncoding regulatory RNAs with a 5‐terminal phosphoryl group and a 3‐terminal hydroxyl group and is approximately 22 nucleotides in length . More than 1/3 of all human genes are controlled by miRNA . Increasing evidence has suggested the important role of miRs in the progression of BC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egy miRNS-nek a bá-zispárosodás szabályai szerint több célgénje is van, és egy célmolekula kifejeződését számos miRNS is szabályoz-hatja. A biológiai funkciók hátterében álló mechanizmusokat a sejten belüli jelátviteli útvonalakkal lehet a leginkább jellemezni, így a miRNS-ek szabályozó szerepét nemcsak egy-egy génhez (1. táblázat) [34,42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], hanem egy-egy jelátviteli útvonalhoz is lehet rendelni.…”
Section: A Mirns-ek áLtal éRintett Jelátviteli úTvonalak Az Agyalapimunclassified